Свойства водных cуспензий глинистых минералов, активированных переменным электромагнитным полем - Кадошников, В.М.; Забулонов, Ю.Л.; Литвиненко, Ю.В.; Макаров, А.С.; Савицкий, Д.П. (Мінералогічний журнал, 2010)
Рассмотрено влияние переменного электромагнитного поля на реологические свойства водных суспензий, приготовленных из глин Черкасского месторождения. Показано, что активация бентонитовых и палыгорскитовых глин переменным электромагнитным полем с частотой 5,2 кГц существенно увеличивает структурную вязкость растворов. Свойства глинистых суспензий определены природой глинистого минерала и длительностью электромагнитной обработки. Обработка электромагнитным полем монтмориллонитовой и палыгорскитовой глин в течение 1—10 мин увеличивает структурную вязкость в 2—10 раз, что связано с диспергацией глинистых агрегатов до более мелких частиц в коагуляционной системе. Обработка полиминеральной глины, представляющей собой генетическую смесь палыгорскита и монтмориллонита, вызывает уменьшение структурной вязкости, что связано с изменением самоорганизованных пространственных структур и разрушением межфазных гидратных слоев между их элементами. Розглянуто вплив перемінного електромагнітного поля на реологічні властивості водних суспензій, виготовлених з глин Черкаського родовища. Показано, що активація бентонітових та палигорськітових глин пере мінним електромагнітним полем з частотою 5,2 кГц суттєво збільшує структурну в’язкість розчинів. Властивості глинистих суспензій визначені природою глинистого мінералу та тривалістю електромагнітної обробки. Обробка електромагнітним полем монтморилонітових і палигорськітових глин протягом 1—10 хв збіль шує структурну в’язкість у 2—10 разів, що пов’язано з диспергацією глинистих агрегатів на дрібніші частинки у коагуляційній системі. Обробка полімінеральної глини, що є генетичною сумішшю палигорськіту і монтморилоніту, призводить до зменшення структурної в’язкості, пов’язаного зі зміною самоорганізованих просторових структур і руйнуванням міжфазних гідратних шарів між їх елементами. The effect of alternating electromagnetic field on the rheological properties of aqueous suspensions, prepared from the clay of the Cherkassy deposit has been studied. In the process of the study the following materials were used: bentonite clay from productive layer of the Cherkassy deposit of bentonite clays and palygorskite clays (second layer), containing not less than 85 % of montmorillonite; palygorskite clay (clay from the third layer), as the clay mineral containing not less than 95 % of palygorskite; polymineral clay (clay from the fourth layer) represented by the genetic mixture of palygorskite and montmorillonite. The peculiarity of the latter is an extremely small amount of clay crystallites. It is shown that the processing of clay suspensions by the alternating electromagnetic field with frequency of 5.2 kHz causes significant changes in the structure of clay solutions. Under the influence of electromagnetic field the structural viscosity of aqueous suspensions of bentonite clays and palygorskite clays has increase. An increase of structural viscosity of clay suspensions is determined by the nature of clay mineral and duration of electromagnetic treatment. For aqueous suspensions the clay processing by electromagnetic field for 10 min under the same conditions increases the viscosity of montmorillonite suspension 10—15 times, for palygorskite — 2—3 times. Stability of activated coagulation systems to mechanical stress is much less in comparison with the initial suspensions of bentonite clays and palygorskite clays. In contrast to suspensions of bentonite clays and palygorskite clays the processing of an aqueous clay suspension and clay of the fourth layer for 1—10 min under the same conditions reduces the structural viscosity of the intact (original) suspension 1.5—2 times. This character is retained for the partially damaged suspension. The main reason for increasing the structural viscosity of the clays of the second and third layers is the increase in the number of structural elements in the coagulation system due to dispersion of the clay aggregates to smaller particles, while for the clay suspensions of the fourth layer the decrease of structural viscosity is mainly connected with the change of selforganized spatial structures in coagulation system and the destruction of interphase hydration layers between the structure elements. Processing of water clay suspensions by electromagnetic field leads to the formation of coagulation structures unstable in time. The relaxation time of the activated structures is determined by the nature of clay minerals and duration of electromagnetic treatment and it is no less than 100 hours.